Posterior ischemic optic neuropathy following continuous renal replacement therapy: a case report - Hiro Takefuji; Junpei Komagamine (International Journal of Emergency Medicine)
Abstract Background Posterior ischemic optic neuropathy (PION) is a rare cause of acute vision loss in intensive care unit patients. PION following continuous renal replacement therapy (CRRT) hemodialysis has not ever been reported. Here, we report a case of bilateral nonarteritic PION following the initiation of CRRT. Case presentation A 52-year-old man with hypertension and stage 4 chronic kidney disease was admitted due to metabolic acidosis, hyperkalemia, and acute exacerbation of CKD. CRRT caused transient hypotension upon initiation but corrected the metabolic acidosis and hyperkalemia six hours after initiation. Therefore, CRRT was stopped. However, several hours after the cessation of CRRT, the patient experienced sudden, painless vision loss in both eyes. Assessment of his visual acuity revealed the inability to perceive light in both eyes. There were no symptoms or signs of giant cell arteritis. An ophthalmological examination revealed no abnormalities. Magnetic resonance imaging of the brain revealed no compressive lesions or acute stroke, but magnetic resonance angiography revealed stenosis of both the bilateral carotid artery and the right middle cerebral artery. Administration of a high dose of corticosteroids did not reverse his vision loss. Thus, nonarteritic PION following CRRT was diagnosed. Conclusions PION should be considered if a patient with multiple vascular risk factors complains of sudden painless vision loss without signs of optic disk edema after the initiation of CRRT. Preventing blood pressure drops during the initiation of CRRT in patients with multiple vascular risk factors may prevent PION.